Web Design and Application Programming Interface (API) Smart Farming Application - Annafi' Franz; Eko Junirianto; Suswanto (TEPIAN, 2021)
Agriculture in Indonesia plays a very important role. But the agricultural sector also has a lot of crowds in the process, from the nursery process to the feeding process to the harvesting process, especially when the current Corona pandemic is very influential, for that we need special attention from the parties involved in overcoming the existing problems. In agriculture these processes become more effective and efficient so as to increase the level of productivity of agricultural products. One way to overcome this problem is to involve technology which is currently developing rapidly. The technology that will be built will be able to help the agricultural management process which can be called smart agricultural technology. Technology is able to collect data and present hydroponic plant data during the planting process so that appropriate action can be taken immediately. The technology that will be built in the form of a Web and API (Application Programming Interface) in smart farming applications is expected to be able to make the planting management process more effective and efficient.